2 K cryogenic system development for superconducting cavity testing of CiADS. (April 2021) - Xiao-fei, Niu; Feng, Bai; Xian-jin, Wang; Peng, Zhang; Yong-hui, Yang; Jun-hui, Zhang; Da-ming, Sun
Highlights: A 2 K cryogenic system was developed for superconducting cavity testing of CiADS and HIAF projects. The major equipment were described in detail, new structures are used in the design. Measuring methods and instruments at 2 K temperature level were studied. The first cooling down experiment of the cryogenic system was carried out successfully. Abstract: Cryogenic system working at 2 K is crucial for superconducting accelerator. A 70 W@2 K cryogenic system was developed for the testing of superconducting cavities used in the China Initiative Accelerator Driven System (CiADS). There will be more than 257 superconducting radio frequency (SRF) cavities to be vertically tested in the next three years. The system is designed with 2 testing dewars and the cool down/warm up processes of two dewars can be conducted simultaneously, so that the interval between each test can be reduced to minimum. The system process was designed and heat loads were analyzed under practical conditions. The parameters' calculation and design of the core equipment, such as sub-atmospheric heat exchanger, valve box, vertical testing dewar, and vacuum pump set, are described in detail. First cooling down experiment was carried out successfully, realizing a continuous cooling down process from 300 K to 4.5 K in 30 h, and then reaching 2 K in another 2.5 h.